Linear Finite Element Approximations for the Timoshenko Beam and the Shallow Arch Problems (Journal of Computational Mathematics, 2002)
In this paper we discuss the linear finite element approximations for the Timoshenko beam and the shallow arch problems with shear dampening and reduced integration. We derive directly the optimal order error estimates uniformly with the small thickness parameter, without relying on the theory of saddle point problems.